2021
DOI: 10.3389/fphar.2021.794417
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Improving Aspirin Resistance: Blood-Activating Herbs Combined With Aspirin in Treating Atherosclerotic Cardiovascular Diseases

Abstract: Atherosclerotic thrombotic disease continues to maintain a high morbidity and mortality rate worldwide at present. Aspirin, which is reckoned as the cornerstone of primary and secondary prevention of atherosclerotic cardiovascular diseases (ASCVDs), has been applied in clinics extensively. However, cardiovascular events continue to occur even though people utilize aspirin appropriately. Therefore, the concept of aspirin resistance (AR) was put forward by scholars, which is of great significance for the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
3
0
1
Order By: Relevance
“…Aspirin, as a typical antiplatelet therapy for secondary stroke prevention (Wang et al, 2022;Zhao et al, 2021). In our study aspirin un-efficacy were wide-ranging, but all reasons happened with few cases such as frequency of DVT, stroke in coronary artery, brain stroke, TIA and blood clotting event with prolong use of aspirin.…”
Section: Egyptians Saudismentioning
confidence: 47%
“…Aspirin, as a typical antiplatelet therapy for secondary stroke prevention (Wang et al, 2022;Zhao et al, 2021). In our study aspirin un-efficacy were wide-ranging, but all reasons happened with few cases such as frequency of DVT, stroke in coronary artery, brain stroke, TIA and blood clotting event with prolong use of aspirin.…”
Section: Egyptians Saudismentioning
confidence: 47%
“…Several Chinese medical herbs have been suggested as alternative treatments for patients with aspirin resistance [ 114 , 115 ]. For example, a study conducted by Liao et al in a zebrafish vascular disease model demonstrated that leonurine, a chemical isolated from Leonurus japonicus, a flowering plant, reduces platelet activity.…”
Section: Alternative Antiplatelet Therapies For Aspirin Resistant Vas...mentioning
confidence: 99%
“…Основными проблемами антиагрегантной терапии ишемического инсульта (ИИ) являются резистентность, которая на терапии ацетилсалициловой кислотой достигает 24-36 % [1], клопидогрелом -32-45 % [2], и развитие геморрагических осложнений, встречающихся с частотой 1,0-11,6 % [3]. Частота церебральных геморрагических осложнений (образование внутримозговой гематомы, геморрагическая трансформация ишемического очага) составляет 1,2-1,4 % случаев [4], желудочно-кишечных кровотечений -1-3 % [5].…”
Section: введение / Introductionunclassified